In situ high‐temperature X‐ray diffraction study of Sc‐doped titanium oxide nanocrystallites. Issue 6 (13th October 2020) - Zenou, Victor Y.; Bertolotti, Federica; Guagliardi, Antonietta; Toby, Brian H.; Von Dreele, Robert B.; Bakardjieva, Snejana
Abstract : Rietveld and Debye function analyses of X‐ray diffraction data, combined with high‐resolution transmission electron diffraction and nitrogen sorption techniques, were used to investigate annealed 4 at.% Sc‐doped anatase. Abstract : Titanium dioxide is an inexpensive wide‐gap highly ionic semiconductor with striking photocatalytic capabilities in several heterogeneous photoredox reactions. A small crystal size is desirable to maximize the surface area, since photocatalytic reactions occur at the surface of a photocatalyst. Presented here are the synthesis and microstructural characterization of 4 at.% Sc‐doped TiO2 (4SDT) prepared by water‐based co‐precipitation. The crystal structure of 4SDT was examined via in situ high‐temperature powder X‐ray diffraction experiments from 25 to 1200°C. Rietveld analysis revealed single‐phase anatase up to 875°C, while at 900°C the anatase‐to‐rutile phase transformation occurred and at higher temperatures additional reflections of Sc‐rich phases (Sc2 TiO5 from 975°C and Ti3 Sc4 O12 or Sc2 O3 at 1200°C) were observed. Debye function analysis (DFA) was applied to model the total scattering pattern directly in reciprocal space, allowing the reconstruction of Ti vacancies. Both Rietveld and DFA methods were applied to estimate the nanocrystallite size and shape with consistent growth in crystallite size with temperature: an ellipsoid shape with equatorial ∼4.7 nm / axial (001) ∼6.9 nm at 25°C to equatorial ∼27.9 nm / axial (001) ∼39.6 nm at 900°C refined by Rietveld analysis, versus a cylinder shape with D a, b = 4.3 nm and size dispersion σ ab = 1.5 nm, L c = 4.9 nm and σ c = 2.3 nm at 25°C to D a, b = 21.4 nm, σ ab = 8.3 nm, L c = 23.9 and σ c = 10.9 nm at 900°C estimated by DFA. The microstructural changes obtained by Rietveld and DFA methods were supported by high‐resolution transmission electron microscopy image analysis, as well as by the less direct nitrogen sorption techniques that provide information on the size of non‐agglomerated and dense particles. The Ti site‐occupancy factor showed a linear increase from 0.6–0.8 at 25°C to unity at 900°C for anatase, and from ∼0.7 at 900°C to unity at 1200°C for rutile, via Rietveld analysis and DFA.